2018
DOI: 10.1371/journal.pone.0206177
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtype diversity, transmission networks and transmitted drug resistance amongst acute and early infected MSM populations from Coastal Kenya

Abstract: BackgroundHIV-1 molecular epidemiology amongst men who have sex with men (MSM) in sub-Saharan Africa remains not well characterized. We aimed to determine HIV-1 subtype distribution, transmission clusters and transmitted drug resistance (TDR) in acute and early infected MSM from Coastal Kenya.MethodsAnalysis of HIV-1 partial pol sequences from MSM recruited 2005–2017 and sampled within six months of the estimated date of infection. Volunteers were classified as men who have sex with men exclusively (MSME) or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
(64 reference statements)
4
15
0
Order By: Relevance
“…Similar to K103N, M184V/I and Y181C can also be stably passaged without drug pressure [ 26 ] which may be the reason for the higher frequency of these drug resistance mutations in the transmission network. This finding was also observed in other undeveloped [ 25 ] and developed settings [ 27 , 28 ]. The widespread use of ART may have led to a considerable increase in HIV drug resistance and drug resistance transmission in newly infected individuals.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to K103N, M184V/I and Y181C can also be stably passaged without drug pressure [ 26 ] which may be the reason for the higher frequency of these drug resistance mutations in the transmission network. This finding was also observed in other undeveloped [ 25 ] and developed settings [ 27 , 28 ]. The widespread use of ART may have led to a considerable increase in HIV drug resistance and drug resistance transmission in newly infected individuals.…”
Section: Discussionsupporting
confidence: 84%
“…Among 40 drug resistance clusters, K103N was observed in 22 clusters as the common drug resistance site and was the most frequent drug resistance-associated mutation. The possible reason might be that K103N mutation can persist without drug pressure and promote infection to another host [23,24], which has been attributed to the widespread use of NNRTI in first-line ART [25]. Similar to K103N, M184V/I and Y181C can also be stably passaged without drug pressure [26] which may be the reason for the higher frequency of these drug resistance mutations in the transmission network.…”
Section: Discussionmentioning
confidence: 99%
“…MSM-exclusive and IDU-exclusive clusters were more common than FSW and HET clusters. High rates of clustering among MSM and IDU have been described before, both in our setting and elsewhere, and have been linked to an elevated risk of infection among MSM and IDU within close networks 6,8,17,29,30,41 . Whereas the MSM sequences were found in several smaller clusters, the vast majority of the IDU sequences formed one large cluster.…”
Section: Discussionsupporting
confidence: 68%
“…Sequences sampled from the same individuals were excluded from the data set, retaining only the oldest sequence per participant. Risk group information was obtained from LANL and any missing data were obtained by communication with study authors or inferred from reviewing literature from the respective studies 6,[8][9][10][11][12][13][14][15] . In addition, new HIV-1 pol sequences were generated from samples collected 2005-2019 participants in an acute HIV-1 infection cohort and from a prospective observational study following high-risk volunteers in an HIV-1 vaccine feasibility cohort described elsewhere 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Information on HIV drug resistance among MSM in Africa is limited. In prior studies from Kenya and Nigeria, the rates of drug resistance among MSM who reported that they were ART-naive or initiating ART were 8.2% ( Hassan et al, 2018 ) and 9.7% ( Crowell et al, 2020 ), respectively. The study from Nigeria also detected drug resistance in 43% of ART-experienced MSM ( Crowell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%